2015
DOI: 10.1590/0103-6440201302442
|View full text |Cite
|
Sign up to set email alerts
|

Self-Etch Adhesive Systems: A Literature Review

Abstract: This paper presents the state of the art of self-etch adhesive systems. Four topics are shown in this review and included: the historic of this category of bonding agents, bonding mechanism, characteristics/properties and the formation of acid-base resistant zone at enamel/dentin-adhesive interfaces. Also, advantages regarding etch-and-rinse systems and classifications of self-etch adhesive systems according to the number of steps and acidity are addressed. Finally, issues like the potential durability and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
136
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(163 citation statements)
references
References 58 publications
4
136
0
9
Order By: Relevance
“…As part of this behavior, self-etching hydrophilic commercial blends are formulated to change the smear layer with acidic monomers rather than remove it, creating a permeable membrane by smear layer and smear plugs (20,8). This contributed to µTBS results in this study, as there were no statistically significant differences between each other in central and proximal dentin, and still presented higher µTBS values compared to etch-and-rinse adhesives systems in proximal dentin.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As part of this behavior, self-etching hydrophilic commercial blends are formulated to change the smear layer with acidic monomers rather than remove it, creating a permeable membrane by smear layer and smear plugs (20,8). This contributed to µTBS results in this study, as there were no statistically significant differences between each other in central and proximal dentin, and still presented higher µTBS values compared to etch-and-rinse adhesives systems in proximal dentin.…”
Section: Discussionmentioning
confidence: 93%
“…The second is to not exceed the necessary amount of water, avoiding the dilution of some adhesive monomers and phase separation, leading to an improper functionality (14,19). In this case, the self-etching technique has the advantage of a more adaptable approach depending of the intrinsic subtract re-moisture (8,13,20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The self-etching primer, TP, contains 4-META in the solution. 4-META is expected to play important roles in dentin bonding, such as demineralizing of the smear layer, promotion of monomer penetration into dentin and possibly chemical bonding to dentin minerals 28) . Yoshida et al 29) reported chemical bonding strength of several acidic monomers to hydroxyapatite (HAp).…”
Section: Discussionmentioning
confidence: 99%